2018
DOI: 10.1007/s11033-018-4553-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miRNAs related to angiogenesis and adipogenesis in subcutaneous fat of obese and nonobese women

Abstract: To disclose the mechanisms surrounding obesity, we selected microRNAs (miRNAs) that target genes involved in adipogenesis, angiogenesis, and inflammation and compared their expression levels in the subcutaneous adipose tissue of 40 obese and nonobese women. Mature miRNAs were extracted from subcutaneous adipose tissue samples that were collected during surgery and quantified by real-time polymerase chain reaction. miR-16 was overexpressed in the nonobese group (n-expression ratio = − 151.1; P < 0.001). Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Extensive studies have demonstrated that abnormal expression of miRNAs is associated with lipid metabolism disorder and atherosclerosis progression (Aryal et al, 2017; Feinberg & Moore, 2016). Emerging evidence suggests that miR‐424‐5p is involved in metabolic diseases, such as diabetes and obesity (Gasparotto et al, 2019; Wang et al, 2020). Interestingly, miR‐424‐5p is lowly expressed in the peripheral blood isolated from patients and rats with atherosclerosis (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have demonstrated that abnormal expression of miRNAs is associated with lipid metabolism disorder and atherosclerosis progression (Aryal et al, 2017; Feinberg & Moore, 2016). Emerging evidence suggests that miR‐424‐5p is involved in metabolic diseases, such as diabetes and obesity (Gasparotto et al, 2019; Wang et al, 2020). Interestingly, miR‐424‐5p is lowly expressed in the peripheral blood isolated from patients and rats with atherosclerosis (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that miR-424 expression levels were closely associated with fat deposition in women (30); hence, in the present study, it was questioned whether a similar expression pattern would be observed in children. In the current study, the expression levels of miR-424 in the adipose tissue of obese and non-obese children were compared.…”
Section: Introductionmentioning
confidence: 68%
“…Functionally, the expression of miR-424 was identified to be regulated by PPAR-γ, an important transcription factor during adipogenesis (32). Interestingly, in non-obese women, those with higher fat droplet measurements had upregulated expression levels of miR-424 (30). These reports provided novel information about the role of miR-424 in obesity.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…miRNA-18b-3p, identified by RNA-seq, inhibits chicken intramuscular adipocyte differentiation by targeting ACOT13 (Sun et al, 2019). Some miRNAs have also been identified as DE-miRNAs by previous RNA-seq studies related to lipid deposition, including miR-20b, miR-424-3p, miR-486-5p, and let-7f-3p (Hosui et al, 2017;Gasparotto et al, 2019;Huang et al, 2019;Ylioja et al, 2019). Interestingly, miR-664a and miR-542-5p were shown to play an important role in skeletal muscle development (Cai et al, 2018;Ji et al, 2020).…”
Section: Discussionmentioning
confidence: 98%